Fabrication and characterization of polysulfone reinforced hollow fibre membrane. Issue 17 (29th July 2021) - Turken, Turker; Sengur-Tasdemir, Reyhan; Urper-Bayram, Gulsum Melike; Gunes, Oguz; Ates-Genceli, Esra; Tarabara, Volodymyr V.; Koyuncu, Ismail
ABSTRACT: In this study, reinforced hollow fibre membranes were fabricated using different molecular weights of polyvinylidene prolidone (PVP Mw: 10, 40 and 360 kDa) and different take-up speeds (1, 2, 2.6 and 3.5 m/min). Prepared reinforced hollow fibre membranes were characterized in terms of permeability; surface morphology and hydrophilicity; pore size distribution; bovine serum albumin (BSA) rejection and flux recovery ratio. Optimum permeability and BSA rejection were obtained when PVP molecular weight was 40 kDa. After PVP molecular weight determination, advancing speed was changed and it was seen that increasing advancing speed ended up with decreased membrane wall thickness; however, decreased wall thickness increased the probability of irreversible fouling. GRAPHICAL ABSTRACT: UF0001